Utilization of Black Soldier Fly (BSF) Larvae as a Biodecomposer for Compost Production from Kirinyuh and Kepok Banana Waste - Riama Rita Manullang; Rusmini; Faradilla; La Mudi (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
Kirinyuh (Chromolaena odorata L.) is a shrub weed commonly found in open land, with the potential to be used as compost material. However, in the composting process, obstacles arise due to the high cellulose content in the kirinyuh stems. Therefore, a decomposer is needed to help break down the cellulose in the kirinyuh stems. One decomposer with the ability to break down quickly is the Black Soldier Fly (BSF) larvae, commonly known as maggots. The aim of this study is to determine the duration of compost production with the addition of maggots and to compare the results with the standard compost. The research was conducted from June to September 2024. The study consists of two treatments: P0, which is without maggots (control), and P1, which is treated with 5 grams of maggots. The results of the study show that in treatment P0, the compost was ready for use on day 21, while in treatment P1, it was ready on day 18. According to its element content, the compost produced from treatment P1 was better than that from treatment P0. Treatment P1 met the compost standards, while treatment P0 did not meet the standards, especially in terms of potassium (K).